IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK DARI TINDAK KEKERASAN DI KOTA BEKASI - Permana Nurhuda, Rizki; Lituhayu, Dyah; Larasati Setianingsih, Endang (Journal of Public Policy and Management Review, 2024)
The high incidence of child abuse places the city of Bekasi as the third highest in West Java Province in 2023, with a total of 220 cases. Therefore, the Bekasi City government has taken steps to prevent and reduce child abuse through Bekasi Mayor Regulation Number 01 of 2021 concerning Child Protection in Bekasi City. This study aims to determine the implementation of the Bekasi City Government's policy in protecting children from abuse and to identify the factors influencing its implementation. The method used in this research is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. This study employs Van Meter and Van Horn's policy implementation theory. The results of this study indicate that the implementation of the child protection policy against violence in the field is still not optimal due to several obstacles, namely, the lack of coordination and collaboration between agencies, low community participation in counseling, limited staff in the field of child rights fulfillment and in the field of prevention and handling of violence against women and children, and communication barriers with related agencies. The recommendations provided by the researchers include the need for additional educational and health facilities, regular monitoring, the immediate establishment of the P3A Technical Implementation Unit in Bekasi City, prioritizing the construction of physical child protection homes, and developing clear SOPs for the management of child protection homes.